PENGARUH IDIOSINKRATIK KIM JONG UN TERHADAP KEBIJAKAN LUAR NEGERI KOREA UTARA STUDI KASUS MENINGKATNYA ESKALASI KONFLIK DI SEMENANJUNG KOREA (2013) - Siswoyo, Reestya Dyahwatie (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis study discusses about Kim Jong Un’s idiosyncratic impact in North Korea's foreign policy related to the escalation of the conflict in the Korean Peninsula in 2013. The background of this research is the change of North Korea’s foreign policy in the leadership era of Kim Jong Un which decided to re-confrontation with South Korea. Those became the main platform issues examined in this research, which is why North Korea under the leadership era of Kim Jong Un decided to re-confrontation with South Korea in 2013. Those problem will be analyzed and explaned by using idiosyncratic theory, authoritarian leadership and decision making as the basic argument. Based on the theoretical approach that given, it can be deduced that the escalation of the conflict in the Korean Peninsula in 2013 was effected by idiosyncratic of Kim Jong Un that describes the characteristics of Kim Jong Un is dictatorial. Thus, the holder of the power taken by Kim Jong Un so that can be affect the decision making of Kim Jong Un and produce a confrontational North Korea’s policy.Key words: Foreign Policy, Idiosyncratic, Authoritarian Leadership, Decision MakingDOI:https://doi.org/10.33005/jgp.v3i01.1964